Intestinal Parasitic Infections and Associated Risk Factors Among School-going Children of Age 1-5 years in Dharan, Eastern Nepal - Limbu, Dhiren Subba; Shrestha, Samana; Bantawa, Kamana; Majhi, Ramesh; Kharel, Milan (Himalayan Journal of Science and Technology, 2021)
Intestinal parasitic infections have been a major public health burden of developing countries, especially in children. Higher prevalence has been reported among school children, mostly in rural areas of Nepal where water, toilets, hygiene, and sanitation facilities are insufficient. This cross-sectional study was carried out from April to September 2019 to determine the prevalence of intestinal parasitic infections among school-going children1-5 years of Dharan, Nepal, and to assess the associated risk factors. Stool samples were collected in a clean, dry, screw-capped, and wide-mouthed plastic container, kept in an icebox, and transported to the laboratory. Data relating to different risk factors were collected from the parents of 116 participants using a structured questionnaire. The parasites were identified by using the direct wet mount method and formal-ether concentration method. Pearson’s chi-square test was carried out to establish associations between dependent and independent variables using SPSS version 20, and the test considered a greater than < 0.05% as statistically significant with a 95% confidence level. Out of the 116 stool samples, 9 (7.75%) tested positive for the parasitic infections in which 5 (55.5%) were protozoa and 4 (44.45%) were helminths. The prevalent parasites, were Entamoeba histolytica (23%), Hyamenolepis nana (22%), Giardia lamblia (11%), Hookworm (11%), Entamoeba coli (11%), Ascaris lumbricoides (11%), and Intestinal parasitic infections had a significant association with drinking water, bowel syndrome, bathing habit, toilet facility, and washing hands after toilets (p<0.05). Lack of toilets, poor hygiene, and unsafe drinking water were the main risk factors. Improved hygienic practices, safe drinking water, and the use of latrines could lower the rate of parasitic infections.